'Popular' Imagery in the Late Ottoman Periphery: The Wall Paintings in Village Mosques of Denizli Province. (November 2019) - Değirmenci, Tülün
Among the spaces conveying rich information on Anatolian social structure, mosques occupy a special place. In pre-modern societies, village and small-town mosques were not only places of worship, but served as foci of education and sociability, hosting visitors or travellers on occasion. While the architecture of village mosques is usually very simple, the furnishings can be elaborate, turning these modest structures into mirrors reflecting village culture, and thereby the culture of the Ottoman periphery. The present article focuses on eighteenth- and nineteenth-century painted mosques in the Turkish province of Denizli and environs, which display a remarkable unity of style and iconography. In the secondary literature, these works of art usually appear as products of so-called 'Westernization'. By contrast, this study argues that they are outputs of Ottoman popular culture. Tangible from the seventeenth century onwards, the sociocultural dynamics and life practices specific to the Ottoman periphery have given this artwork its peculiar form. Thus, this study encourages researchers to rethink Anatolian conservatism, as it demonstrates that in the pre-modern era, mosques were not the well-protected spaces, distant from everyday life that they are today. Rather, in the period under study, village mosques could be 'ambiguous' spaces seamlessly joining varying spheres of life and belief.